The use of Hax and Meal Method in the Disaggregation Process on the Development of Master Production Schedule. A case Study on a Healthy Drink Industry â€œDIAâ€ Malang - Sucipto, Sucipto; Santoso, E.F. Sri Maryani; Purwandari, Purwandari (Jurnal Teknologi Pertanian, 2005)
The objective of this research is to develop master production schedule (MPS) to meet all consumersâ€™ demand by means of disaggregation process method. The method was applied on a small scale industry producing a several instant powder drinks of the following raw materials: ginger, â€œkunyit putihâ€ (white turmeric); â€œtemulawakâ€ (kind of wild ginger); turmeric and tamarind; â€œkunci sirihâ€ (bettle vine with finger-roots), â€œberas kencurâ€ (lesser galangal and rice), and aloe. The products are packed in two sizes i.e. a sachet of 100 gram (a small sachet) and 250 gram (a big sachet) respectively. Initially, the demand was forecasted using an additive decomposition method, then followed by an aggregated planning based on a work force method and finally, to run a disaggregation process using The Hax and Meal method. The results suggested that for the coming 3 months ought to produce an instant powder of ginger drinks as many as 4,710 small sachets and 1,530 big ones; 4,330 small sachets and 1,416 big ones of white turmeric (Curcuma saffron) instant powder; 3,660 small sachets and 1,100 big sachets of wild ginger (Curcuma xananthorrhiza) instant powder; 2,940 small sachets and 964 big ones of white turmeric-tamarind mixture;Â  1,980 small sachets and 648 big sachets of bettle vine-finger-roots mixture; 2,080 small sachets and 648 big sachets of a lesser galangal-rice mixture; and 2,150 small sachets and 704 big sachets ofÂ  aloe powder respectively. Â  Key Words: hax and meal method, disaggregation, master production schedule